BIM-based model for sustainable built environment in Saudi Arabia - Hasanain, Fatma A.; Nawari, Nawari O. (Frontiers in Built Environment, 2022)
Building Information Modeling (BIM) has had a tremendous impact on the building industry by increasing performance, productivity, and cost-effectiveness. The integrative nature of BIM technology renders it an ideal platform for implementing sustainable strategies in the new construction, renovation, and retrofit of existing structures. In the years 2018-2020, Saudi Arabia’s market gasoline prices have dropped dramatically, necessitating the Kingdom to establish its 2030 vision. The 2030 vision aims to make the Kingdom of Saudi Arabia (KSA) an ideal sustainable society by reducing its reliance on petrol and creating more sustainable buildings and infrastructures. There is an imperative need to translate the green aspirations of the KSA into enforceable regulations. In order to achieve this vision, consistency across jurisdictions is needed to allow robust and well-informed decision-making in adopting and enforcing sustainability. Thus, this research intends to develop a standard metric using the Rule-based BIM model for examining the sustainability of the built environment in Saudi Arabia. The model is proposed to be a standardized measure for addressing the critical elements of the 2030 vision in Saudi Arabia or any other country in similar climatic conditions. Due to the limited number of green buildings in Saudi Arabia, this study aims to formulate a new BIM-based model for Sustainable Built environments in Saudi Arabia that supports the Kingdom’s 2030 vision. This research follows a mixed methodology that includes both qualitative and quantitative approaches. The limitations of the proposed model are presented along with future phases of the study.